2023
DOI: 10.1111/acel.13775
|View full text |Cite
|
Sign up to set email alerts
|

Dietary choline intake is necessary to prevent systems‐wide organ pathology and reduce Alzheimer's disease hallmarks

Abstract: There is an urgent need to identify modifiable environmental risk factors that reduce the incidence of Alzheimer's disease (AD). The B‐like vitamin choline plays key roles in body‐ and brain‐related functions. Choline produced endogenously by the phosphatidylethanolamine N‐methyltransferase protein in the liver is not sufficient for adequate physiological functions, necessitating daily dietary intake. ~90% of Americans do not reach the recommended daily intake of dietary choline. Thus, it's imperative to deter… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 58 publications
2
29
0
Order By: Relevance
“…Tg2576 mice also lack tau pathology. However, MCS has now demonstrated structural/functional benefits in several AD-relevant models, namely Tg2576 (this report), APP/PS1 (Alldred et al 2021;Dave et al 2023), Ts65Dn (Velazquez et al 2013;Powers et al 2016;Strupp et al 2016;Powers et al 2017;Alldred et al 2021;Alldred et al 2023) and 3xTg mice (Dave et al 2023). Moreover, increasing evidence suggests that humans with AD have low serum choline and are improved by dietary choline (Dave et al 2023;Judd et al 2023a;.…”
Section: Limitationsmentioning
confidence: 81%
See 1 more Smart Citation
“…Tg2576 mice also lack tau pathology. However, MCS has now demonstrated structural/functional benefits in several AD-relevant models, namely Tg2576 (this report), APP/PS1 (Alldred et al 2021;Dave et al 2023), Ts65Dn (Velazquez et al 2013;Powers et al 2016;Strupp et al 2016;Powers et al 2017;Alldred et al 2021;Alldred et al 2023) and 3xTg mice (Dave et al 2023). Moreover, increasing evidence suggests that humans with AD have low serum choline and are improved by dietary choline (Dave et al 2023;Judd et al 2023a;.…”
Section: Limitationsmentioning
confidence: 81%
“…In Alzheimer's disease (AD), changes to the diet have been recommended (Bourre 2006;Power et al 2019;Mao et al 2021;Lobo et al 2022), including MCS (Strupp et al 2016;Velazquez et al 2020;Dave et al 2023;Judd et al 2023a;. One reason for the recommendation is that serum levels of choline are low in individuals with AD (Dave et al 2023;Judd et al 2023b).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study showed Grin2A protein expression significantly decreases in the absence of choline, which is further exacerbated in an AD mouse model, suggesting this defect is due to alterations of postsynaptic protein concentrations secondary to insufficient choline. 128 Previous studies have shown differential synaptic and peri-or extra-synaptic localization of these subunits, which can be exchanged by lateral diffusion to finely modulate synaptic strength. 129 Perhaps even more intriguing, ratio imbalances between Grin2a and Grin2b increased cognitive decline and activation of Grin2b containing receptors has been linked to AD due to glutamate excitotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Upregulation of NMDA receptor subunits Grin2a and Grin2b is found in trisomic mice with Grin2a significantly reduced in disease diet, which was corroborated by qRT‐PCR, and Grin2b partially attenuated. A recent study showed Grin2A protein expression significantly decreases in the absence of choline, which is further exacerbated in an AD mouse model, suggesting this defect is due to alterations of postsynaptic protein concentrations secondary to insufficient choline 128 . Previous studies have shown differential synaptic and peri‐ or extra‐synaptic localization of these subunits, which can be exchanged by lateral diffusion to finely modulate synaptic strength 129 .…”
Section: Discussionmentioning
confidence: 99%
“…taurodeoxycholic acid [39], nicotinamide [40], ascorbic acid (vitamin C) [41], Dpantothenic acid (vitamin B5) [42,43] and choline [44] (Figure 4C). Similar to shamF, casM mice also showed an enrichment of anti-oxidative metabolites likely derived from plant-based foods, including ganoderenic acid C [45], oleuropeic acid [46], fasciculol C [47], graveoline [48] (Figure 4C).…”
Section: Metabolomic Feminization and Taurine Enrichment In Castrated...mentioning
confidence: 99%